The Educational Radicalism of Bob Moses - Gillen, Jay (Radical Teacher, 2024)
Those who come in contact with the Algebra Project, founded 40 years ago by Bob Moses, tend to underestimate the extraordinary radicalism of Dr. Moses’s strategy for using math literacy as an organizing tool. The Algebra Project uses hard-earned insights from the Black freedom struggle to create space for young people to fashion their own insurgency. The goal of the Project is the destruction of caste in the United States, approached through the counter-intuitive vehicle of math classrooms.